Helianthus Annuus Seed Hydro-Alcoholic Extract Chemical Composition and Effects on Body Weight and Blood Parameters among Iraqi Patients Suffering from Type 2 Diabetes Mellitus - Noor Al-Huda Saeed; Hussein Hamzah Israa; Abdolmajid Ghasemian (Fasa University of Medical Sciences, 2022)
Background & Objectives: The purpose of the present study was to calibrate and analyze the effects of Helianthus annuus (H. annuus) seeds extract on body weight and blood parameters of type-2 diabetic-mellitus (T2DM) patients. Materials & Methods: Three-hundred cases of T2DM patients were involved in this study including 180 males and 120 females and divided into two groups (each with 150 members). The herbal extract of H. annuus with a concentration of 500mg/kg was subjected to group1 (case population), but group 2 received normal diet for three months. Gas Chromatography mass spectrometry (GC/MS) was used to analyze H. annuus compounds. Results: Major H. annuus fraction included chlorogenic acid (CGA) being 40%. The extract conferred significant decreasing effects on hypertension but not body weight and body mass index (BMI) values. The extract receiving group vs control group regarding the mean blood factors respectively included fast blood glucose (FBS) (39.2% vs 3.22%, p<0.0001), cholesterol (6.9% vs 3.22%, p=0.0237), triglyceride (5.4% vs 2.30, p=0.0113), and increase in high-density lipoprotein (HDL) (22.3% vs 5.26%, p<0.001) and low-density lipoprotein (LDL) (1% vs 2.6%, p=0.0112).   Conclusion: H. annuus major compounds included CGA (40%) contributed to the control of the hypertension, lipid profile and the blood factors among T2DM patients compared to those patients who received normal diet. More detailed investigations by participation of higher number of patients are required in this regard.